Association of educational environment with the prevalence of myopia: a cross-sectional study in central China - Peng, Wei; Zhang, Zikang; Wang, Fei; Sun, Shaoming; Sun, Yining (Frontiers in Public Health, 2023)
Purposes This study was to estimate the prevalence of myopia among primary school students in Hefei, China, and evaluate the association of educational environment with myopia. Methods This study was a cross-sectional study, and recruited primary school students in grades 1–6. Children underwent a stepwise ophthalmic examination, which included visual acuity and objective cycloplegic refraction to identify children with myopia. Under the guidance of parents, children completed a questionnaire, including gender, region, grade and several indicators related to education. The study analyzed the risk factors by using a logistic regression and assessed feature importance by using a random forest algorithm. Results A total of 3,596 primary school students were involved in this analysis, and the overall prevalence of myopia was 27.1%. Gender, grade, education level of the father, education level of the mother, academic level of children, hours of homework per day on weekends, number of after-school tutoring per week and frequency of extracurricular reading were significantly associated with myopia. There was no significant association between the amount of homework per day on school days and myopia after adjusting for covariates. In terms of educational environment, the top 3 factors were academic level of children, homework on weekends and after-school tutoring. Conclusions Educational environment with high educational loads was associated with the high prevalence of myopia. Reducing the burden of studying, especially that after class, was an effective way to prevent myopia.